Lateral Meniscal Posterior Root Repair With Anterior Cruciate Ligament Reconstruction Better Restores Knee Stability. Issue 1 (January 2019) - Tang, Xin; Marshall, Brandon; Wang, Joon Ho; Zhu, Junjun; Li, Jian; Smolinski, Patrick; Fu, Freddie H.
Background: The effect of lateral meniscal posterior root tear and repair—commonly seen in clinical practice in the setting of anterior cruciate ligament (ACL) reconstruction—is not known. Purpose/Hypothesis: This study evaluated the effect of tear and repair of the lateral meniscal posterior root on the biomechanics of the ACL-reconstructed knee. It was hypothesized that anterior tibial translation would increase under anterior loading and simulated pivot-shift loading with the root tear of the posterior lateral meniscus, while repair of the root tear would reduce it close to the noninjured state. Study Design: Controlled laboratory study. Methods: Thirteen fresh-frozen adult human knees were tested with a robotic testing system under 2 loading conditions: (1) an 89.0-N anterior tibial load applied at full extension and 15°, 30°, 60°, and 90° of knee flexion and (2) a combined 7.0-N·m valgus and 5.0-N·m internal tibial torque (simulated pivot-shift test) applied at full extension and 15° and 30° of knee flexion. The following knee states were tested: intact knee, ACL reconstruction and intact lateral meniscus, ACL reconstruction and lateral meniscal posterior root tear, and ACL reconstruction and lateral meniscal posterior root repair. Results: In the ACL-reconstructed knee, a tear of the lateral meniscal posterior root significantly increased knee laxity under anterior loading by as much as 1 mm. The transosseous pullout suture root repair improved knee stability under anterior tibial and simulated pivot-shift loading. Root repair improved the ACL graft force closer to that of the native ACL under anterior tibial loading. Conclusion: Lateral meniscal posterior root injury further destabilizes the ACL-reconstructed knee, and root repair improves knee stability. Clinical Relevance: This study suggests a rationale for surgical repair of the lateral meniscus, which can restore stability close to that of the premeniscal injury state.